Vitiligo Coexistent with Nevus Depigmentosus: This Was Treated with Narrow-Band UVB and These Lesions Were Followed Using the Mexameter®, a Pigment-Measuring Device - Hwang, Seon-Wook; Kang, Ju-Hyun; Jung, So-Young; Choi, Joon-Hee; Seo, Jong-Keun; Lee, Deborah; Sung, Ho-Suk (Annals of dermatology, 2010)
Nevus depigmentosus (ND) is a congenital, non-progressive, hypopigmented lesion that is usually stable throughout an affected individual's lifetime. The clinical features of vitiligo are similar to those of ND, but the two diseases have different treatment responses and prognoses. We report here on a rare case of vitiligo that was coexistent with ND. Both conditions were treated with narrow-band UVB. An 11-year-old boy presented with two distinct types of hypopigmented lesions, one on the forehead and the other on his back. The first was a hypopigmented patch with leukotrichia, and it was incidentally discovered 3 months before the child was examined at our clinic and it had rapidly increased in size. The second hypopigmented patch was detected at birth and it had slowly been increasing in size. The hypopigmented lesion on the child's forehead was diagnosed as vitiligo, and the one on his back as ND. Once- or twice-weekly narrow-band UVB treatment was initiated. Improvements in the two lesions were assessed with clinical photography and using a Mexameter® (Courage-Khazaka Electronic, Germany), which is a pigment-measuring device.